Pengaruh Harga terhadap Kepuasan Pelanggan Jasa Transportasi Online - Amanda Diamontina; Susanto; Yuliana (Journal of Trends Economics and Accounting Research, 2023)
This research aims to find out whether there is an influence of price on customer satisfaction with online transportation services (Case Study of Medan Cendana Polytechnic Students, Academic Year 2020-2021). The author uses associative quantitative research methods. Associative research is a research method that asks questions between 2 or more variables. The data collection technique used by the author in this research was a closed questionnaire. The sample used was 51 students of Cendana Polytechnic, Medan for the 2020-2021 academic year. The data analysis technique used is simple linear regression. Based on calculations carried out by the author using the SPSS version 23 program application, the r square result was 29.1% and the remaining 70.9% was influenced by other factors not tested in this study. From the regression analysis calculations, the regression equation Y = 15,609 + 0.513X is obtained. The results of the research show that price influences customer satisfaction with online transportation services (Case Study of Cendana Polytechnic Students, Medan, Academic Year 2020-2021).